2022
DOI: 10.1063/5.0124076
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds stress modeling of supercritical narrow channel flows using OpenFOAM: Secondary currents and turbulent flow characteristics

Abstract: In this study, the full Launder, Reece and Rodi pressure-strain model and nonlinear boundary damping functions were incorporated in OpenFOAM® to simulate the turbulence-driven secondary currents in supercritical narrow channel flows such as in sediment bypass tunnels (SBTs). Five simulations were performed under uniform flow conditions covering Froude numbers from 1.69 - 2.56 and aspect ratios (channel width to flow depth) ar from 0.9 - 1.91 to investigate the formation of secondary currents and their impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
3
2
0
Order By: Relevance
“…A similar trend was reported in the experiments of Demiral, Boes & Albayrak (2020) and the Reynolds-averaged Navier–Stokes (RANS) simulations of Kadia et al. (2022), who showed that secondary motions in open ducts have a topology similarity to those in closed ducts, although both studies featured flow in ducts with free surface in the supercritical regime, which is rather different from our flow case with a flat top surface. Additionally, RANS simulations should be taken with caution, as the prediction of secondary flows is not always accurate.…”
Section: Mean Flow Structuresupporting
confidence: 90%
See 2 more Smart Citations
“…A similar trend was reported in the experiments of Demiral, Boes & Albayrak (2020) and the Reynolds-averaged Navier–Stokes (RANS) simulations of Kadia et al. (2022), who showed that secondary motions in open ducts have a topology similarity to those in closed ducts, although both studies featured flow in ducts with free surface in the supercritical regime, which is rather different from our flow case with a flat top surface. Additionally, RANS simulations should be taken with caution, as the prediction of secondary flows is not always accurate.…”
Section: Mean Flow Structuresupporting
confidence: 90%
“…The secondary shear stress is nearly negligible on the bottom and sidewalls, although it has a comparable intensity with the other components at the bottom and top corners, suggesting that its mixing action is limited to the corner regions, whereas it is not relevant close to the side and bottom walls. Similar distributions of the Reynolds stresses τ 11 , τ 22 and τ 12 have also been observed in the studies of Demiral et al (2020) and Kadia et al (2022). This general organization is found regardless of the duct aspect ratio, although characterizing differences are visible, which are due to the imprint of the secondary flows.…”
Section: Frictionsupporting
confidence: 79%
See 1 more Smart Citation
“…To achieve these goals, three tests were performed both experimentally and numerically for discharges Q = 0.045 m 3 /s, 0.07 m 3 /s, and 0.095 m 3 /s; approach flow depths h 0 = 0.109 m, 0.151 m, and 0.175 m; aspect ratios a r = 1.83, 1.32, and 1.14; and Froude numbers Fr ≈ 2. These tested a r and Fr values are comparable to that observed in existing SBTs 17 .…”
Section: Introductionsupporting
confidence: 85%
“…The k-x shear stress transport (SST) is one of the main turbulence models that we are aware of. 6,9 The cost and difficulty of this method are lower than DES (detached eddy simulation) and LES (large eddy simulation) according to Refs. 10 and 11.…”
Section: Introductionmentioning
confidence: 99%